Fullerene grafted graphene oxide with effective charge transfer interactions. (October 2016) - Kumar, Rachana; Khan, Saba; Gupta, Neha; Naqvi, Samya; Gaurav, Kumar; Sharma, Chhavi; Kumar, Mahesh; Kumar, Pramod; Chand, Suresh
Abstract: We have covalently grafted fullerene molecules to graphene oxide using hydrolyzed PCBM as fullerene precursor via very mild process without the use of metal catalysts and comprehensively studied the charge transfer interactions in ground and excited state. For the evidence of covalent grafting of fullerene on graphene oxide sheets different spectroscopic studies have been performed like, FTIR, Raman spectroscopy, UV–vis absorption, cyclic voltammetry, XRD and XPS. Amount of loading of fullerene on graphene oxide is calculated by thermogravimetric analysis and morphological study was performed by AFM and TEM. Covalently attached fullerene molecules act as excellent electron acceptor for ultrafast electron transfer from graphene oxide sheets and established by photoluminescence and ultrafast pump-probe transient absorption (TA) spectroscopy. From the TA measurements, we reveal ultrafast charge separation and long lived charge separated species formation in fullerene functionalized graphene oxide.